2019
DOI: 10.1093/ibd/izy398
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Engraftment and Efficacy of Fecal Microbiota Transplant for Clostridium Difficile in Patients With and Without Inflammatory Bowel Disease

Abstract: Background: Recurrent and severe Clostridium difficile infections (CDI) are treated with fecal microbiota transplant (FMT). Uncertainty exists regarding FMT effectiveness for CDI with underlying inflammatory bowel disease (IBD) and regarding its effects on disease activity and effectiveness in transferring the donor microbiota to patients with and without IBD.Methods: Subjects with and without IBD who underwent FMT for recurrent or severe CDI between 2013 and 2016 at The Mount Sinai Hospital were followed for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 32 publications
1
41
1
Order By: Relevance
“…The absence of complete engraftment is consistent with findings in other disease states such as C. difficile disease and IBD, where there is not complete replacement of the recipient's microbiome with the donor's microbiome, yet clinical benefits and changes in the microbiome with FMT have been observed [ 28 30 ]. This suggests that the effects of the microbiome may not be dependent upon a single organism or group of organisms but rather on the functionality of the microbiome.…”
Section: Discussionsupporting
confidence: 80%
“…The absence of complete engraftment is consistent with findings in other disease states such as C. difficile disease and IBD, where there is not complete replacement of the recipient's microbiome with the donor's microbiome, yet clinical benefits and changes in the microbiome with FMT have been observed [ 28 30 ]. This suggests that the effects of the microbiome may not be dependent upon a single organism or group of organisms but rather on the functionality of the microbiome.…”
Section: Discussionsupporting
confidence: 80%
“…Human subjects: All individuals of age 18 and over were recruited in the study using a protocol approved by the Mount Sinai Institutional Review Board (HS# 11-01669). The donors and patients who received FMT for rCDI or rCDI and IBD were described in a previous study analyzed with 16S rRNA amplicon sequencing 69 .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a unique risk to the IBD population is the risk for flare of underlying IBD, which in one study was reported to be as high as 25.6% in IBD patients receiving FMT for recurrent CDI [ 36 ]. Nevertheless, a different study examining FMT in IBD patients with recurrent CDI reported no serious AEs [ 44 ]. A Cochrane meta-analysis examining FMT as a treatment for IBD included an analysis of 277 patients for serious AEs, indicating that 10/140 (7%) who received FMT experienced a serious AE compared to 7/137 (5%) in the control group (RR 1.40, 95% CI 0.55–3.58, I2 = 0%) [ 45 ].…”
Section: Case Discussionmentioning
confidence: 99%